Structure of the digital scientific revolution - Leciejewski, Sławomir Grzegorz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Nowadays, computers are in common use, both in experimental and theoretical research. It is worth considering if the implementation of a new, universal research tool has significantly changed the science of the end of 20th century. The crucial question which I will try to answer is if computers have revolutionized the scientific research. In order to find the answer, I will describe modern digitally aided science, taking into consideration the research conducted in the greatest elementary physics laboratory. Subsequently, I will refer to the classic concept of scientific revolution proposed by Thomas S. Kuhn. Finally, I will answer the question related to digital revolution in science.